2008
DOI: 10.3748/wjg.14.5046
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings in patients with upper gastrointestinal bleeding clinically classified into three risk groups prior to endoscopy

Leonardo Tammaro,
Maria Carla Di Paolo,
Angelo Zullo
et al.

Abstract: AIM:To investigate in a prospective study whether a simplified clinical score prior to endoscopy in upper gastrointestinal bleeding (UGIB) patients was able to predict endoscopic findings at urgent endoscopy. METHODS: All consecutive UGIB patients referred to a single endoscopic center during a 16 mo period were enrolled. Before endoscopy patients were stratified according to a simple clinical score (T-score), including T1 (high-risk), T2 (intermediate-risk) and T3 (low-risk). Endoscopy was performed in all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
2
14
1
5
Order By: Relevance
“…It has been reported previously that UGIB patients are predominantly male (ranging between 60% -80%) [11,12], and comparably, in our study, we found that 56% of all patients were male.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been reported previously that UGIB patients are predominantly male (ranging between 60% -80%) [11,12], and comparably, in our study, we found that 56% of all patients were male.…”
Section: Discussionsupporting
confidence: 76%
“…Likewise, Tammaro L. et al [12] also revealed an older age of their patients; the mean age of their patients was 65 years. Similarly, our study showed that the majority of UGIB cases presented in the later stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a number of scoring systems have been developed for these patients [7,[9][10][11]. Moreover, surveys have been conducted in different countries to assess local standard treatment features [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The T-score can be used to triage patients who are likely to have high-risk endoscopic stigmata and therefore need intervention [24] . It has the ability to predict high-risk endoscopic stigmata, rebleeding and mortality with an accuracy similar to the GBS [65] .…”
Section: The Importance Of Outcomesmentioning
confidence: 99%
“…An Italian study developed the T-score which included 4 clinical parameters commonly assessed in the UGIB setting: (1) general conditions (poor, intermediate, good); (2) pulse (< 90 beats/min, 90-110 beats/min, > 110 beats/min); (3) systolic blood pressure (< 90 mmHg, 90-110 mmHg, > 110 mmHg); and (4) haemoglobin level (≤ 8 g/dL, 9-10 g/dL, > 10 g/dL) [24] (Table 7).…”
Section: Scores With Clinical Variables Onlymentioning
confidence: 99%